Influence Debt Defaults, Current Ratio, Return On Assets And Sales Growth On Acceptance Of Audit Opinion Going Concern Subsector Textiles And Garments - Windy Winata; Helmina Putri Bungsu; Helena Lestari Sibuea; Ramlan Am Silitonga; Benny Rojeston Marnaek Nainggolan; Dokman Marulitua Situmorang (Jurnal Ipteks Terapan, 2023)
This research aims to make the textile and garment industry make a significant contribution to economic growth as well as creating sizable job opportunities, and industry this Also push enhancements investment in the And outside country. method data collection in this study was carried out by means of a documentation study which is technique collections with method, notes, gather, And learn data company related problem which currently researched. population used in study this is 43 financial statements of textile and garment companies listed on the Indonesia Stock Exchange with taking sample which based on consideration amount sample which meet the sample selection criteria of 10 companies with 3 years of observation so that the research sample obtained as many as 30 samples for research data DER.CR partially has a significant effect on GCAO in textile and sub-sector companies garment while ROA, SG partially have no significant effect on GCAO (Y) on company subsector textiles And garment so that Debt default, Current ratio, ROA And Sales growth simultaneously affects GCAO in textile subsector companies And garment.